Philolanguaging Religious Education toward the Context of Inclusivity - Temporal, Wilson (International Journal of Arts, Sciences and Education, 2021)
The context of delivering Religious Education in Catholic schools must be inclusive of any faith or religion through what maybe possibly called as the ethics of communication. Hence, this paper aimed to synthesize the philosophical concepts and interpretations on language as applied in Education to determine an excellent framework reference for a more meaningful way of teaching Religious Education. Specifically, it ascertained the way how Religious Education is currently taught in Catholic schools, the meaningful use of language, and the possible misconceptions that could be addressed with a sound philosophy of language and philosophy of education. This paper employed the documentary analysis which covered a range of meta-synthesis methods including critical interpretive synthesis and thematic analysis. Careful analysis show that varied cultural, religious, and spiritual worldviews should be a point of consideration in lieu of giving emphasis to the prominence of the Catholic Faith and Tradition. Religious Education in Catholic schools needs to be tolerant with non-Catholic Christians and non-Christians as it tries to keep its social teachings and moral dispositions as well. It should be well noted that the language of faith is not a kind of reasoning but a matter of discipline or attitude that reflects human values. Hence, the language of religious education is proposed to be relearned in the context of Ludwig Wittgenstein’s philosophy of language. Keywords: meaning, myth, values, philosophy of language, religious education